New Technologies in the Development of Empathy: Benefits and Threats - Anna Maria Pawiak (Horyzonty Wychowania)
RESEARCH OBJECTIVE: The objective of this analysis is to explore the potential of new technologies in enhancing the empathy skills of modern users.